2016
DOI: 10.18632/oncotarget.11599
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol induced G0/G1/S phase arrest and apoptosis in melanoma cells via AKT/MAPK pathway

Abstract: Both preclinical and epidemiology studies associate β-adrenoceptors-blockers (β-blockers) with activity against melanoma. However, the underlying mechanism is still unclear, especially in acral melanoma. In this study, we explored the effect of propranolol, a non-selective β-blocker, on the A375 melanoma cell line, two primary acral melanoma cell lines (P-3, P-6) and mice xenografts. Cell viability assay demonstrated that 50μM-400μM of propranolol inhibited viability in a concentration and time dependent manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 44 publications
0
69
0
Order By: Relevance
“…It was previously shown that Prop reduces intracellular calcium levels, Bax-mediated cytochrome C release and inhibits protein kinase C (PKC) activity in a β-adrenoreceptor independent manner [1921], and it induces cell cycle arrest and apoptosis via Akt/MAPK pathway in melanoma cells [22]. Many studies in humans have demonstrated its efficacy for the treatment of infantile haemangioma.…”
Section: Introductionmentioning
confidence: 99%
“…It was previously shown that Prop reduces intracellular calcium levels, Bax-mediated cytochrome C release and inhibits protein kinase C (PKC) activity in a β-adrenoreceptor independent manner [1921], and it induces cell cycle arrest and apoptosis via Akt/MAPK pathway in melanoma cells [22]. Many studies in humans have demonstrated its efficacy for the treatment of infantile haemangioma.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, propranolol, a commercial nonselective β-AR blocker, is now recommended as an important drug in first-line treatment against IH [25,26]. Although propranolol shows remarkable response rates, there are still some major adverse effects, such as changes in sleep, acrocyanosis, hypotension, and hypoglycemia, which raise serious clinical concerns [27,28]. IH pathogenesis, especially the mechanism associated with hypoxic proliferation, awaits urgent clarification.…”
Section: Discussionmentioning
confidence: 99%
“…Among the signalling pathways involved in melanoma growth, NA acting on β 1 ‐ and β 2 ‐adrenoceptors activates the Gs/cAMP/PKA pathway thus leading to increased expression of VEGF and inflammatory cytokines (Yang et al ., ; Deng et al ., ). In addition, in human melanoma cells, propranolol has been found to inhibit the Akt and MAPK pathways thus promoting apoptosis and decreasing cell viability (Zhou et al ., ). Moreover, in mouse melanoma cells, propranolol prevents the activation of different pathways including the activation of Akt, STAT3 and iNOS (Dal Monte et al ., ).…”
Section: β‐Adrenoceptor Signalling In Melanomamentioning
confidence: 97%
“…In melanoma cells, propranolol prevents the NA‐induced cell proliferation, likely through the activation of apoptotic processes (Dal Monte et al ., ; Moretti et al ., ; Calvani et al ., ; Wrobel and Le Gal, ; Zhou et al ., ). In mouse models of melanoma, propranolol delays primary tumour growth and metastasis development, thus reducing melanoma progression and improving the survival rate (Hasegawa and Saiki, ; Glasner et al ., ; Barbieri et al ., ; Wrobel and Le Gal, ; Wrobel et al ., ; Zhou et al ., ; Kuang et al ., ; Maccari et al ., ).…”
Section: Introductionmentioning
confidence: 98%